Overview of the Association Between Non-Alcoholic Fatty Liver Disease and Hypertension - Niki S. Kakouri; Costas G. Thomopoulos; Eirini P. Siafi; Angeliki E. Valatsou; Kyriakos S. Dimitriadis; Iliana P. Mani; Sotirios P. Patsilinakos; Dimitrios M. Tousoulis; Konstantinos P. Tsioufis (Cardiology Discovery)
Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease, and its prevalence is rising. NAFLD is closely associated with metabolic syndrome, with both conditions sharing common clinical characteristics such as obesity, insulin resistance, type 2 diabetes mellitus, hypertension, and hypertriglyceridemia. Several observational studies have evaluated the relationship between NAFLD and hypertension, with the overall evidence suggesting a bidirectional relationship. It is hypothesized that activation of the sympathetic nervous and renin-angiotensin systems, observed in NAFLD with or without insulin resistance promotes the development of hypertension. In patients with hypertension, activation of these systems can lead to hepatic fibrosis and progressive inflammation through increased oxidative stress and activation of hepatic stellate cells and Kupffer cells. The present review examines the pathophysiologic and clinical evidence supporting the bidirectional association between NAFLD and hypertension.